DETERMINATION OF THE IMPERVIOUS SURFACES IN AN URBAN DEVELOPMENT AREA USING GIS METHODS (PANGEEA, 2025)
Impervious surfaces can cause environmental problems, including flooding and contaminated runoff. There is little visibility of private paving. Infrared aerial photos can be used for the build-up to map this paving that can be used to add the correct areas to sewer hydraulic models. Chlorophyll from plants absorbs infrared light, making it possible to filter out unpaved surfaces from infrared images. In particular, driveways and paved front gardens are thus insightful and are included in the runoff areas of the sewer systems. This analysis provides a true-surface map for private paving. However, not including these pavements in sewer calculations produces a result that matches measurements better in most situations, due to the walk-in model used. The private pavements have their own characterization which allows them to be easily adjusted or switched on and off, for example depending on the type of analysis being performed. With the output from this analysis, the governments can be better equipped to prevent floodings and human or material damages
Keywords: impervious; GIS; urban; pavement; flood